1970
DOI: 10.1002/cpt1970115740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L‐dopa alone and in combination with an extracerebral decarboxylase inhibitor on blood pressure and some cardiovascular reflexes

Abstract: L‐Dopa produced a significant reduction in recumbent and standing blood pressure in patients with neurologic or psychiatric disorders. The addition of an extracerebral decarboxylase inhibitor potentiated this effect. Reflex forearm arteriolar and venous constriction was present during therapy with L‐dopa alone or in combination with the decarboxylase inhibitor, but there was an attenuation of reflex forearm arteriolar constriction. It is suggested that the hypotensive effect of L‐dopa may be mediated through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1971
1971
1980
1980

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Dihydrogenation decreases their ability to cause peripheral vasospasm. The overall cardiovascular effect of both ergot derivatives is, like levodopa, to induce hypotension (Watanabe, Chase & Landon, 1970;Greenacre, Teychenne, Petrie, Calne, Leigh & Reid, 1976); however, as with levodopa, continued administration of lergotrile induces tolerance to this hypotensive effect (Calne & Teychenne, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Dihydrogenation decreases their ability to cause peripheral vasospasm. The overall cardiovascular effect of both ergot derivatives is, like levodopa, to induce hypotension (Watanabe, Chase & Landon, 1970;Greenacre, Teychenne, Petrie, Calne, Leigh & Reid, 1976); however, as with levodopa, continued administration of lergotrile induces tolerance to this hypotensive effect (Calne & Teychenne, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…This evidence, however, does not support the possibility raised by Gross et al (1972) that postural hypotensionc can be explained by a central mechanism. Calne et al (1970) and Watanabe et al (1970) both presented clinical evidence that patients treated with L-DOPA who had supine hypotension had a greater fall in blood pressure when erect (postural hypotension). These two groups (Watanabe et al, 1970;Calne, Petrie, Rao, Reid & Vakil, 1972) reported that postural hypotension was not improved when lower doses of L-DOPA were combined with a peripheral dopa-decarboxylase inhibitor, although Calne et The results of the present investigation as well as other studies have been examined in terms of hypotheses which may possibly explain the extracerebral mechanism of L-DOPA-induced postural hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Both orthostatic (postural) and supine hypotension (usually referred to as hypotension) have been observed in man (Calne, Brennan, Spires & Stern, 1970;Watanabe, Chase & Cardon, 1970). There is substantial evidence from animal experiments that hypotension is due to a central mechanism whereby L-DOPA is effective after conversion to dopamine and/or noradrenaline in certain areas of the brain (Henning & Rubenson, 1970a;Robson, 1971;Minsker, Scriabine, Stokes, Stone & Torchiana, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, patients became hypotensive. Hypotension is especially marked in the standing position but recumbent blood pressure also appears to be lowered (4,19). Furthermore, inhibition of extracerebral decarboxylase appears to potentiate the hypotensive effect of L-dopa (19).…”
Section: Effect Of L-dopamentioning
confidence: 99%